양성 전립선질환 환자에서 혈청 전립선특이항원 수치는 외래에서 측정한 수치보다 입원해서 측정한 수치가 감소한다 - Yoon, In Seok (The Graduate School, Ajou University, 2013)
Purpose: To investigate whether the hospitalization itself may influence the serum PSA values. Materials and Methods: Transrectal ultrasound-guided prostate biopsies were performed for detecting prostate cancer in 2,017 patients between February 2001 and April 2011 at our institution. Among them, 416 patients who were hospitalized for prostate biopsies, whose serum PSA values were checked at outpatient department (OPD) within 1 month before admission and also just after admission, and who had negative prostate biopsy results were included. We retrospectively reviewed the data of 416 patients and compared the serum PSA values checked at OPD and during hospitalization. Results: Among total 416 patients, the interval between the two PSA measurements was 22.2 days (3-30 days) and the prostate size measured by transrectal ultrasonography was 53.63 cc (12.8-197.9cc). Among total 416 patients, mean serum PSA levels checked during hospitalization were significantly lower than those checked at OPD (6.69 ng/ml vs. 8.01 ng/ml, p<0.001). When stratified according to age, the presence or absence of chronic prostatitis in biopsy pathology, serum PSA levels, and prostate size, the serum PSA levels checked during hospitalization were significantly lower than those checked at OPD in all subgroups, except in cases with ages of 20-39 years and PSA <4 ng/ml, which showed no significant differences. Conclusions: Hospitalization itself decreases the serum PSA values compared to those checked at OPD in patients with benign prostatic diseases. Therefore, the serum PSA values should be checked on an OPD basis for the serial monitoring of PSA levels.
학위논문(석사)아주대학교 일반대학원 :의학과,2013. 8
Keywords: Hospitalization; Outpatient clinics; Prostate-specific antigen